MEASUREMENT OF SKY BRIGHTNESS USING SKY QUALITY METER FOR DETERMINING DARK LOCATION OF ASTRONOMICAL OBSERVATION AND DETERMINATION OF TWILIGHT IN BANGKA ISLAND - Sukma, Mega
Light pollution is a broad term that refers to a number of problems, all of which are caused by the inefficiency of using artificial light. Light pollution is a type of waste that comes from culture, the environment, and waste in energy use. By utilizing Sky Quality Meter (SQM), the brightness of the sky can be measured objectively. SQM can also be used to measure the level of light pollution in a place. The impact of this light pollution is that it has an impact on the science of astronomy, astronomers are the most disadvantaged because in the process of research or data collection on celestial bodies it is considered very difficult due to too bright reflections from lights so that the magnitude of a star looks faded. Sky brightness using SQM can be used as an astronomical instrument to determine the time of dawn and dusk when the sun cannot be observed directly because the sun is still below the horizon. This study examines light pollution in six locations using SQM LU-DL and SQM LU-DL-V, especially in Bangka Island. The data obtained from SQM is graphed so that it can be seen the transition from night to night to morning. The darker the sky, the higher the brightness level and the better as a place for astronomical observations. Results The darkest location is in the Bangka Induk area Bakam Village 22,24 mpsas and the brightest location is in the Ketawai Beach area, Central Bangka Regency with a sky brightness value of 16.54 mpsas. Areas with high light pollution have sky brightness of 12-13 mpsas in the horizon direction, and 16 mpsas in the zenith direction. Areas with low light pollution have a sky brightness of 17-18 mpsas in the horizon direction, and 20-21 mpsas in the zenith direction. Regression correlation between sky brightness and solar depression angle is 0.79±0,04 with depression angle range between -10,800 and -17,460. The zenith direction SQM tends to have a deeper depression angle than the east direction